Strategi Pemasaran Produk Olahan Rumput Laut dalam Mendukung Pariwisata di Desa Kertasari Kabupaten Sumbawa Barat - Bayu Ardi Angga; Muhamad Johari; Hariono (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2022)
Management of seaweed into a consumable product is one method of increasing the selling price of seaweed. There are groups of processors and marketers of processed seaweed products in the form of ready-to-eat products, such as seaweed lunkhead, seaweed sticks, and seaweed crackers in Kertasari Village, Taliwang District, West Sumbawa Regency. However, the low demand for these seaweed products is due to a lack of marketing. The research method used in this study is descriptive qualitative research. This study's data came from both primary and secondary sources. Observation, interviews, and documentation were used to collect data. Qualitative data techniques were used in the analysis. According to the findings of this study, there are six alternative strategies that can be implemented: maintaining product quality, cooperating with the government, creating cooking classes, developing new products, marketing via social media, and determining strategic locations.